Sweat distribution and perceived wetness across the human foot: the effect of shoes and exercise intensity - West, A. M.; Tarrier, J.; Hodder, S.; Havenith, G. (Ergonomics, 2019)
This study investigates foot sweat distribution with and without shoes and the relationship between foot sweat distribution and perceived wetness to enhance guidance for footwear design. Fourteen females performed low-intensity running with nude feet and low- and high-intensity running with shoes (55%VO2max and 75%VO2max, respectively) on separate occasions. Right foot sweat rates were measured at 14 regions using absorbent material applied during the last 5 min of each work intensity. Perceptual responses were recorded for the body, foot and four foot regions. Foot sweat production was 22% greater nude (p < .001) and with shoes did not increase with exercise intensity (p = .14). Highest sweat rates were observed at the medial ankle and dorsal regions; lowest sweat rates at the toes. Perceptions of wetness and foot discomfort did not correspond with regions of high sweat production or low skin temperature but rather seemed dominated by tactile interactions caused by foot movement within the shoe.